FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN BIDAN DALAM PENCEGAHAN INFEKSI PENULARAN HIV/AIDS PADA PERTOLONGAN PERSALINAN DI KABUPATEN TABALONG - Lestari, Nur Cahyani Ari; Purwanti, Sri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
The number of cases of HIV / AIDS sufferers in Tabalong Regency from 2018-2019 has fluctuated. Preliminary interviews with several midwives, most of whom did not know about HIV / AIDS infection and its dangers, only a small proportion (35%) of BPS attended APN training. The purpose of this study was to analyze the relationship between education, knowledge and attitudes of BPS with HIV / AIDS infection prevention measures in childbirth assistance in Tabalong Regency, South Kalimantan Province. Analytical survey research design, observational method with cross sectional study design. The population is all BPS and is active in assisting childbirth, totaling 270 midwives, the sampling method is simple random sampling, a total sample of 60 BPS who actively assist in childbirth. The results showed that 59 (98.3%) BPS had secondary education; 33 (55%) BPS have good knowledge; 41 (68.3%) BPS has a supportive attitude towards the PI action of HIV / AIDS transmission in childbirth assistance; 53 (88.3%) BPS has good action in preventing HIV / AIDS infection during delivery assistance; there is no relationship between BPS education and PI action of HIV / AIDS transmission in delivery assistance (p = 1,000); there is a correlation between BPS knowledge and PI action of HIV / AIDS transmission in delivery assistance (p = 0.002); there was no relationship between BPS attitudes and PI action of HIV / AIDS transmission in delivery assistance (p = 0.668). The conclusion of this research is that there are still BPS who have not reached the tertiary level of education; there are still BPS who have a lack of knowledge about HIV / AIDS this is due to only a small part of them who have been trained in APN, there are a small number of BPS who still show an attitude of not supporting the implementation of PI during delivery assistance, not all BPS perform PI action properly during delivery assistance, For this reason, it is suggested to the Health Office of Tabalong Regency to consider the formulation of health policies, formulate an agenda related to improving the competence of midwives; for IBI, it can facilitate increasing the knowledge and competence of IBI members and can provide motivation to midwives to always carry out PI actions in every delivery assistance.